Gap Control by Singular Schrödinger Operators in a Periodically Structured Metamaterial - Exner, Pavel; Khrabustovskyi, Andrii (Журнал математической физики, анализа, геометрии, 2018)
We consider a family Hεε>0 of εZⁿ-periodic Schrödinger operators with δ′-interactions supported on a lattice of closed compact surfaces; within a minimum period cell one has m ∊ N surfaces. We show that in the limit when ε→0 and the interactions strengths are appropriately scaled, Hε has at most m gaps within finite intervals, and moreover, the limiting behavior of the first m gaps can be completely controlled through a suitable choice of those surfaces and of the interactions strengths. Ми розглядаємо сiм'ю Hεε>0 εZⁿ-перiодичних операторiв Шредiнгера з δ′-взаємодiями, якi локалiзованi на сiм замкнених компактних поверхонь; мiнiмальна комiрка перiодичностi мiстить m ∊ N таких поверхонь. Показано, що при ε→0 i при певному порядку сили взаємодi Hε має на кiнцевих iнтервалах не бiльше m спектральних лакун. Крiм того, гранична поведiнка перших m лакун повнiстю контролюється за допомогою належного вибору цих поверхонь i сили взаємодi .